IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA POWTOON UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PENGAJARAN LAJU REAKSI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher-centered learning tends to limit student engagement, while the use of innovative learning media remains suboptimal. This study aims to determine whether the application of a discovery learning model assisted by Powtoon media can improve student learning outcomes in reaction rate material. The research employed a nonequivalent control group design. The sample consisted of 60 students from SMA Negeri 1 Pagaran in the 2025/2026 academic year, selected through purposive sampling, including 30 students in the XI Science class (experimental group) and 30 students in the XI Applied class (control group). Data were collected using multiple-choice objective tests administered as pre-test and post-test to measure students’ learning outcomes. The results indicated a significant improvement in the experimental class after the implementation of discovery learning assisted by Powtoon media. Based on the N-Gain analysis, the experimental class achieved an average score of 0.79, categorized as high. Furthermore, the Independent Samples t-test on post-test data at a significance level of 0.05 showed a Sig. (2-tailed) value of 0.00. Using a right-tailed test, the significance value (1-tailed) was 0.000 (< 0.05), indicating a statistically significant difference. In conclusion, the application of the discovery learning model assisted by Powtoon media effectively improves student learning outcomes in reaction rate material. Moreover, the improvement in the experimental class is higher compared to the control class that applied conventional learning methods